DETERMINAN KETIMPANGAN PENDAPATAN PULAU KALIMANTAN DAN PULAU SUMATERA - Yulia Fransiska Sembiring; Candra Mustika; Helen Parkhurst (Jurnal Daya Saing, 2026)
Economic development does not only focus on increasing economic growth, but also on ensuring the equitable distribution of development outcomes so that they can be felt by all levels of society. Income inequality indicates that economic growth does not always occur alongside equitable distribution. Income inequality in Kalimantan and Sumatra fluctuated during the 2017–2023 period. This study analyzes the effect of GRDP per capita, local government capital expenditure, and the labor force participation rate on income inequality in both regions. This research uses secondary data with a panel data model, combining time series data from 2017 to 2023 and cross-sectional data from Kalimantan and Sumatra. The analysis applies the Fixed Effect Model approach using EViews 12 software. The data were obtained from the Statistics Indonesia (BPS) and local government publications. The results show that, partially, GRDP per capita has a negative and significant effect on income inequality in both Kalimantan and Sumatra. Meanwhile, local government capital expenditure and the labor force participation rate do not have a significant effect on income inequality in either region. The findings also show that income inequality in Kalimantan, at 0,320, is higher than in Sumatra, at 0,318. Therefore, the most influential factor affecting income inequality in Kalimantan and Sumatra is GRDP per capita